1991
DOI: 10.1073/pnas.88.24.11535
|View full text |Cite
|
Sign up to set email alerts
|

How does RNase H recognize a DNA.RNA hybrid?

Abstract: The mechanism of RNase H substrate recognition is proposed from a model of a chemically modified DNA-RNA hybrid Escherichia coil RNase H complex. Sitedirected mutagenesis of the enzyme and substrate titration observed by heteronuclear two-dimensional NMR spectra have been carried out. A model complex has been built, based on free structures of the enzyme and the substrate independently determined by x-ray crystallography and NMR distance geometry, respectively. In addition to steric and electrostatic complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(148 citation statements)
references
References 26 publications
9
138
1
Order By: Relevance
“…Numerous conflicting proposals have been made regarding the number of metal ions necessary for activity and the precise catalytic mechanism of ribonuclease H (5,6,13,15,25,28,37), but a consensus is developing that a single metal is required for activity. It is unclear which co-crystal (Mg 2ϩ or Mn 2ϩ ) most closely approximates the position of the metal in Site 1 during catalysis on a nucleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous conflicting proposals have been made regarding the number of metal ions necessary for activity and the precise catalytic mechanism of ribonuclease H (5,6,13,15,25,28,37), but a consensus is developing that a single metal is required for activity. It is unclear which co-crystal (Mg 2ϩ or Mn 2ϩ ) most closely approximates the position of the metal in Site 1 during catalysis on a nucleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The precise interactions between RNase H and the heteroduplex and the conformation of the DNA/RNA duplex at the active site of the enzyme have been the subject of numerous investigations over the last 15 years (see for example refs 31-34 and cited literature). The enzyme was expected to use the availability of 2′-hydroxyl groups in the RNA strand and the absence thereof in the DNA strand to discriminate between DNA/RNA and RNA/RNA duplexes (31). On the basis of NMR investigations in solution, it was concluded that sugars of the DNA strand in the hybrid duplex adopted Eastern pucker.…”
mentioning
confidence: 99%
“…This glutamine is conserved in the RNase H domain of HIV-1 reverse transcriptase [14], and its counterpart of Thermus thermophilus RNase H is histidine [40], which also can act as a proton donor in a hydrogen bond. The mutation of Gln-72 to alanine, which resulted in a reduced affinity for the substrate [24], also suggests its contribution to the substrate recognition. At position + 1, the backbone amides of Cys-13 reside close to the 2'-hydroxyl.…”
Section: Construction Of a Tertiary Structure Model Of The Enzyme-mentioning
confidence: 99%
“…DNA hybrid duplex was constructed in a manner similar to those described previously [11,24]. The hybrid duplex structure [32] and the crystal structure of RNase HI in complex with a Mg 2÷ ion [12] were manipulated for docking on a computer graphics screen (HYDRA, Polygen).…”
Section: Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation